Methodology series module 7: Ecologic studies and natural experiments - Maninder Singh Setia (Indian Journal of Dermatology, 2017)
In this module, we have discussed study designs that have not been covered in the previous modules – ecologic studies and natural experiments. In an ecologic study, the unit of analysis is a group or aggregate rather than the individual. It may be the characteristics of districts, states, or countries. For example, per capita income across countries, income quintiles across districts, and proportion of college graduates in states. If the data already exist (such as global measures and prevalence of diseases, data sets such as the National Family Health Survey, census data), then ecologic studies are cheap and data are easy to collect. However, one needs to be aware of the “ecologic fallacy.” The researcher should not interpret ecologic level results at the individual level. In “natural experiments,” the researcher does not assign the exposure (as is the case in interventional studies) to the groups in the study. The exposure is assigned by a natural process. This may be due to existing policies or services (example, one city has laws against specific vehicles and the other city does not); changes in services or policies; or introduction of new laws (such helmet for bikers and seat-belts for cars). We would like to encourage researchers to explore the possibility of using these study designs to conduct studies.